Estimación de impactos ambientales basado en el análisis de ciclo de vida de la fase agrícola de la cadena agroalimentaria convencional y agroecológica de la zanahoria (Daucus carota) en las juntas parroquiales "La Esperanza" y "Tabacundo", cantón Pedro Moncayo. - Gavilanes Morales, Denisse Estefanía (2018)
The main objective of the research was to estimate the environmental impacts of water consumption and emission of CO2eq emitted into the atmosphere through the water and carbon footprint indicators in the agricultural phase of the carrot crop of an agroecological and conventional system, from the Esperanza and Tabacundo parishes of the Pedro Moncayo canton. To this end, the methodology used to obtain the water footprint was based on the Manual of Evaluation of the water footprint of Arjen Y. Hoekstra, together with the manual 056 of Evapotranspiration and the software Cropwat 8.0 of the Organization of the United Nations for Agriculture and Food (FAO). The Guidelines of the Intergovernmental Panel on Climate Change (IPCC) for the agriculture sector were followed for calculating the carbon footprint. The research is based on a study of five agroecological and one conventional producers delimiting the functional unit to kilograms of product, obtaining the results for the water footprint on average of the agroecological crops a footprint of 29, 61 l of water / kg of product and for conventional cultivation 759,51 l of water / kg of product. To calculate the carbon footprint, it was determined that the average value of the traces of the agroecological crops is 6.79 kg CO2eq / kg of product and the conventional crop is 394.94 kg CO2eq / kg of product The importance of this research is to denote invisible environmental and social externalities that are generated in both agricultural production systems.